Techniques for measuring the electromagnetic shielding effectiveness of materials. I. Far-field source simulation. - Wilson, P. F.; Ma, M. T.; Adams, J. W.
Shielding effectiveness relates to the ability of a material to reduce the transmission of propagating fields in order to electromagnetically isolate one region from another. Because the shielding capability of a complex material is difficult to predict, it often must be measured. A number of approaches to simulating far-field source are studied, including the use of coaxial transmission-line holders and a time-domain system. In each case, the system frequency range, test sample requirements, test field type, dynamic range, measurement time required, and analytical background are considered. Data taken on a common set of materials are presented
Keywords: ELECTROMAGNETIC MEASUREMENTS; ELECTROMAGNETIC SHIELDING; SYSTEM TESTING; ELECTROMAGNETIC PROPAGATION; COAXIAL COMPONENTS; TRANSMISSION LINES; TIME DOMAIN ANALYSIS; DYNAMIC RANGE; FREQUENCY MEASUREMENT; TIME MEASUREMENT